Buccomaxillofacial clinical approach to the patient with pycnodysostosis: case report and literature review - Silva, Albert da Paixão; Ferreira, Lorena Mendonça; Meza, Daniel Maurício; Santos, Rair de Miranda; Nery, Bruna Borges; Santana, Kalil Ayres; Padilha, Walter Suruagy Motta (Seven Editora, 2023)
Pycnodysostosis is a rare sclerosing skeletal dysplasia, hereditary and of autosomal recessive character, which is characterized by the presence of dense bones and thick cortical area with high fragility in affected individuals. To report a clinical case of pycnodysostosis, associating its clinical and radiographic features and discussing its causes, physiological repercussions and considerations related to orthodontic management and oral and maxillofacial surgical approaches. An 8-year-old female patient, phaeoderma, with pycnodysostosis, short stature, broad hands, dystrophic nails, and shortened phalanges, hypoplastic middle facial third and mandibular micrognathia. Intraoral examination revealed the presence of mixed dentition, crowding in the mandible, prolonged retention of deciduous teeth, multiple dental gyrations, extensive dental caries, absence of dental unit 11, ogival palate, anterior and posterior crossbite on the left side. Knowledge of the clinical manifestations in the oral and maxillofacial region related to pycnodysostosis is essential to identify and prepare an appropriate treatment plan for the development of these changes, which with time become more evident and difficult to manage. DOI: https://doi.org/10.56238/colleinternhealthscienv1-044